The ethics and regulatory landscape of including vulnerable populations in pragmatic clinical trials. (October 2015) - Welch, Mary Jane; Lally, Rachel; Miller, Jennifer E; Pittman, Stephanie; Brodsky, Lynda; Caplan, Arthur L; Uhlenbrauck, Gina; Louzao, Darcy M; Fischer, James H; Wilfond, Benjamin
Policies have been developed to protect vulnerable populations in clinical research, including the US federal research regulations (45 Code of Federal Regulations 46 Subparts B, C, and D). These policies generally recognize vulnerable populations to include pregnant women, fetuses, neonates, children, prisoners, persons with physical handicaps or mental disabilities, and disadvantaged persons. The aim has been to protect these populations from harm, often by creating regulatory and ethical checks that may limit their participation in many clinical trials. The recent increase in pragmatic clinical trials raises at least two questions about this approach. First, is exclusion itself a harm to vulnerable populations, as these groups may be denied access to understanding how health interventions work for them in clinical settings? Second, are groups considered vulnerable in traditional clinical trials also vulnerable in pragmatic clinical trials? We argue first that excluding vulnerable subjects from participation in pragmatic clinical trials can be harmful by preventing acquisition of data to meaningfully inform clinical decision-making in the future. Second, we argue that protections for vulnerable subjects in traditional clinical trial settings may not be translatable, feasible, or even ethical to apply in pragmatic clinical trials. We conclude by offering specific recommendations for appropriately protecting vulnerable research subjects in pragmatic clinical trials, focusing on pregnant women, fetuses, neonates, children, prisoners, persons with physical handicaps or mental disabilities, and disadvantaged persons.